Information-communication technologies in the work of a teacher of physical training - Baluyev, S. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The article presents the options for using information and communication technology in the work activities of a physical education teacher in a general education school, and their strengths and weaknesses are identified. The use of these technologies allows the teacher of physical culture to improve the educational process. The undoubted advantage of using computer tests is a convenient way to perform them and instant processing of the results by online services. Students can independently find, analyze and select the necessary information; it helps them to form core competencies and realize their creative potential. Effective use of Internet resources is necessary for successful practical activities of a physical education teacher, helps to acquire certain professional competencies, changes the educational process according to the needs of our time.